Tannin-tolerant and extracellular tannase producing Bacillus isolated from traditional fermented tea leaves and their probiotic functional properties - Kridsada Unban (2020)
© 2020 by the authors. A total of 117 Bacillus strains were isolated from Miang, a culture relevant fermented tea of northern Thailand. These strains were collected from 16 sampling sites in north Thailand. In this collection 95 isolates were tannin-tolerant Bacillus capable of growth on nutrient agar supplemented with 0.5% (w/v) total tannins from tea leaves extract (TE). The strains were also positive for pectinase, xylanase and amylase activity, while 91 and 86 isolates were positive for cellulase and βmannanase, respectively. Only 21 isolates producing extracellular tannase were selected for further characterization. Identification by 16S rRNA gene sequence analysis revealed that more than 50% (11 of 21 isolates) were Bacillus tequilensis, whereas the remaining were B. siamensis (3), B. megaterium (3), B. aryabhattai (3) and B. toyonensis (1). B. tequilensis K34.2 produced the highest extracellular tannase activity of 0.60 U/mL after cultivation at 37 °C for 48 h. In addition, all 21 isolates were resistant to 0.3% (w/v) bile salt, sensitive to gentamicin, erythromycin, vancomycin and kanamycin and also tolerant to acidic condition. Cell hydrophobicity varied from 9.4 to 80.4% and neutralized culture supernatants of some Bacillus isolates showed bacteriocin producing potentiality against Samonella enterica serovar Typhimurium TISTR 292. All tested probiotic properties indicated that B. tequilensis K19.3, B. tequilensis K34.2 and B. siamensis K19.1 had high probiotic potential. This is the first report describing tannin-tolerant Bacillus and their extracellular tannase producing capability in Miang, a traditional fermented tea of Thailand.